1995
DOI: 10.1002/ar.1092410402
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the morphology and phosphatase cytochemistry of the Golgi region of hepatocytes during the acute phase response to inflammation

Abstract: In hepatocytes from inflamed rats an apparent switch had occurred in the type of secretory material processed by the Golgi apparatus. Furthermore, the inflammation-induced increase in the size of individual Golgi stacks apparently was not due to a parallel increase in size of all Golgi saccules. Rather, saccules within given Golgi compartments responded in a characteristic and specific manner to the increase in glycoprotein processing that occurs during inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
7
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
4
7
0
Order By: Relevance
“…Inflamed rats. A previous study showed that 24 h r following turpentine-injection, the hepatocyte Golgi apparatus contained a granulofilamentous material and few of the lipoprotein particles seen in control rats (Thorne-!Ijomsland and Jamieson, 1995). In the present study, the hepatocyte Golgi apparatus was shown to contain lipoprotein particles in 1 (Figs.…”
Section: Golgi Stackssupporting
confidence: 60%
See 3 more Smart Citations
“…Inflamed rats. A previous study showed that 24 h r following turpentine-injection, the hepatocyte Golgi apparatus contained a granulofilamentous material and few of the lipoprotein particles seen in control rats (Thorne-!Ijomsland and Jamieson, 1995). In the present study, the hepatocyte Golgi apparatus was shown to contain lipoprotein particles in 1 (Figs.…”
Section: Golgi Stackssupporting
confidence: 60%
“…Studies on corresponding changes in the morphology of the hepatocyte Golgi apparatus that processes the primarily glycoprotein (Gordon and Koj, 1985;Jamieson et al, 1987), acute phase reactants have focused on the time interval (24-72 hr) when the serum response is maximal. During this time interval, we (Turchen et al, 1977;Thorne-Tjomsland and Jamieson, 1995) and others (Lombart et al, 1980) have shown the hepatocyte Golgi apparatus to be visibly enlarged. The increase in size has been confirmed quantitatively through morphometric measurements of Golgi diameter and estimations of total Golgi protein/total cell protein (Lombart et al, 1980).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…These findings in invertebrates are substantiated by data in mammals in which biliary secretion and upregulated lipid transport are linked with vesicle production off the Golgi complex. Furthermore, evidence indicates that there is a parallel relationship between expansion of Golgi, particularly the TGN, and its enrichment with acid phosphatase and active phospholipid and cholesterol flow in biliary secretion (Jones et al, 1980;Thorne-Tjomsland and Jamieson, 1995). Similar type of enrichment of Golgi membranes in phosphatidycholine, phosphatidylethano- lamine, and unesterified cholesterol has been reported in lactating rat mammary glands (White et al, 1981).…”
Section: Discussionmentioning
confidence: 78%